2014
DOI: 10.1039/c3ib40215k
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane recovery kinetics of a microfluidic intracellular delivery platform

Abstract: Intracellular delivery of materials is a challenge in research and therapeutic applications. Physical methods of plasma membrane disruption have recently emerged as an approach to facilitate the delivery of a variety of macromolecules to a range of cell types. We use the microfluidic CellSqueeze delivery platform to examine the kinetics of plasma membrane recovery after disruption and its dependence on the calcium content of the surrounding buffer (~5min without calcium vs. ~30s with calcium). Moreover, we ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 30 publications
(55 reference statements)
6
62
0
Order By: Relevance
“…This cell suspension was mixed with a tetramethylrhodamine‐conjugated 10 kDa dextran fluorescent dye and passed through a chip whose constrictions were 7 μm wide ( Figure A). Tetramethylrhodamine‐conjugated dextran was chosen for these experiments for compatibility with downstream FACS analysis; while larger than the 3 kDa cascade blue‐conjugated dextran employed earlier, delivery efficiency is not affected by the molecular weight of dextran . GFP expression in PANC‐1 cells provided an independent signal to confirm successful labeling of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This cell suspension was mixed with a tetramethylrhodamine‐conjugated 10 kDa dextran fluorescent dye and passed through a chip whose constrictions were 7 μm wide ( Figure A). Tetramethylrhodamine‐conjugated dextran was chosen for these experiments for compatibility with downstream FACS analysis; while larger than the 3 kDa cascade blue‐conjugated dextran employed earlier, delivery efficiency is not affected by the molecular weight of dextran . GFP expression in PANC‐1 cells provided an independent signal to confirm successful labeling of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…The microfluidic device has demonstrated applicability in delivering a variety of materials with a wide range of sizes that are retained by the cells, allowing for the manipulation of their biological properties . Here, our use of in vitro CTC models and clinical PDAC patient samples has demonstrated the additional utility of this platform to selectively deliver payload within a heterogeneous population of cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers reported that cyclic stretch affects the mechanical properties of ECs, such as cell proliferation [14], cytoskeletal structure [15], signal transduction [16], and gene expression and transfer [17]. However very few researches have been done to quantify the effect of cyclic stretching on the cellular uptake of NPs [18]. The aim of 2 Journal of Nanomaterials this study is to investigate the effects of cyclic stretch on the cellular uptake of NPs and its dependence on NP size through controlled tests.…”
Section: Introductionmentioning
confidence: 99%